Calculation of temperature distribution and effective temperature in high burnup fuel of WWER-1000; MATEC Web of Conferences; Vol. 194 : Heat and Mass Transfer in the Thermal Control System of Technical and Technological Energy Equipment (HMTTSC 2018) - Kudrov A. I. Alexander Ivanovich (Les Ulis, EDP Sciences, 2018)
Title screen